2014
DOI: 10.1590/0102-311x00150713
|View full text |Cite
|
Sign up to set email alerts
|

Viviendo con trasplante renal, sin protección social en salud: ¿Qué dicen los enfermos sobre las dificultades económicas que enfrentan y sus efectos?

Abstract: Viviendo con trasplante renal, sin protección social en salud: ¿Qué dicen los enfermos sobre las dificultades económicas que enfrentan y sus efectos?Kidney transplant patients without social protection in health: what do patients say about the economic hardships and impact?Viver com transplante renal sem proteção social em saúde: o que os pacientes dizem sobre as dificuldades econômicas e os seus efeitos?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
0
13
0
9
Order By: Relevance
“…These participants reported that what they were living after transplantation was different than health professionals had promised, such as reducing costs, returning to a normal life and achieving an improved quality of life, due the impossibility to continue treatment, in particular, as a result of economic difficulties. Thus, the fear of rejecting the organ due to the absence of immunosuppressive drugs afflicted the people involved in the study (18) .…”
Section: [] I Can't Go To the Beach I Can Go But I Have To Stay Imentioning
confidence: 99%
“…These participants reported that what they were living after transplantation was different than health professionals had promised, such as reducing costs, returning to a normal life and achieving an improved quality of life, due the impossibility to continue treatment, in particular, as a result of economic difficulties. Thus, the fear of rejecting the organ due to the absence of immunosuppressive drugs afflicted the people involved in the study (18) .…”
Section: [] I Can't Go To the Beach I Can Go But I Have To Stay Imentioning
confidence: 99%
“…50% of the population) were enrolled in Seguro Popular (Comisión Nacional de Protección Social en Salud, 2012). However, the plan excluded coverage for the most expensive health conditions, including CKD (Mercado-Martínez et al, 2014).…”
Section: Healthcare Systems and Renal Care In Two Developing Countriesmentioning
confidence: 99%
“…The increased incidence and prevalence of CKD leads to increased demand for the services offered by the health system, which, to date, have been documented as insufficient, and have even been excluded from a significant number of renal patients (Carrillo-Larco;Bernabé-Ortíz, 2018;Mercado-Martínez;Correa-Maurício, 2015;Roberti et al, 2018), since they generated inequities in accessing services, where access is understood as 'the degree to which individuals or groups of individuals have the ability to obtain the necessary care of the provided medical care' (Laurell, 2016;López-Arellano;Jarillo-Soto, 2017). Not to mention the increase in the economic, social and emotional costs implied by this suffering (Díaz-Medina; Mercado-Martínez, 2019; Mercado-Martínez; Hernández-Ibarra, 2016).…”
Section: Introductionmentioning
confidence: 99%